Conversion of Sidewalks into Vendor Stalls: A Case Study on Mardika Street, Sirimau District, Ambon - Oitha, Viona Sofia; Leuwol, Ferdinand Salomo; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This research examines the functional shift of sidewalks into merchant kiosks on Mardika Beach Road, Sirimau District, Ambon. The research type used is a survey method with quantitative and qualitative approaches. The research location is on Mardika Beach Road, with the implementation time from November 16 to December 16, 2023. The research population consisted of 30 merchant kiosks, with a purposive sample of 20 people. Data collection techniques include observation, interviews, documentation, and data analysis. The study results show that the functional shift of sidewalks at Mardika Terminal has positive and negative impacts that need to be considered balanced. Positively, the functional change of sidewalks into trading areas provides economic opportunities for local communities to develop small businesses, create new jobs, and promote economic growth. However, on the other hand, the functional shift of sidewalks has reduced the effectiveness and comfort of pedestrian paths. The sidewalks from Mardika Beach Bridge to the small port have been used as trading locations, resulting in discomfort for pedestrians. Uncontrolled economic activities also impact traffic congestion and environmental cleanliness issues due to scattered waste. Thus, a balance between economic growth and public convenience can be optimally achieved in the Mardika Terminal area, Ambon.